Cytokine profile of bronchoalveolar lavage-derived CD4(+), CD8(+), and gammadelta T cells in people with asthma after segmental allergen challenge - Krug, N; Erpenbeck, V J; Balke, K; Petschallies, J; Tschernig, T; Hohlfeld, J M; Fabel, H (American journal of respiratory cell and molecular biology, 2001)
T cell-derived cytokines play an important role in the pathogenesis of allergic asthma, but little is known about the cytokine profile of their different subsets. The aim of the present study was to investigate the cytokine production potential of CD4(+), CD8(+), or gammadelta(+) T cells derived from the bronchoalveolar space of mild atopic asthmatic subjects (n = 11) and nonatopic control subjects (n = 9) before and 24 h after segmental allergen challenge. The cytokine production was determined using the technique of intracellular cytokine detection by flow cytometry. Comparing asthmatic with control subjects we found no difference in the percentage of CD4(+), CD8(+), or gammadelta T cells in the bronchoalveolar lavage fluid before and after allergen challenge. Before allergen challenge the proportion of cells producing the cytokines interferon (IFN)-gamma, interleukin (IL)-2, IL-4, IL-5, and IL-13 was not different in CD4(+) and CD8(+) cells. The major difference between the groups was an increased percentage of positive-staining cells for the T helper-(Th)2-cytokines IL-5 and IL-13 in the gammadelta T-cell subset. After allergen challenge, all T-cell subsets revealed a decreased proportion of cells producing the Th1-type cytokines IFN-gamma and IL-2. The percentage of IL-4- and IL-5-positive cells did not change in all subsets, and there was a decreased proportion of IL-13- positive cells in the CD4(+) subset. These findings indicate an increased Th2-cytokine profile in gammadelta T cells. After allergen challenge, the dysbalance between Th1 and Th2 cytokines was further accentuated by a reduction in Th1 cytokine-producing T cells.